Difficulties of Vietnamese Students in Learning Academic Writing - Ngo Phan Anh Nghi; Trong Nhan Truong (Research and Education Development (READ) Institute collaborate with Faculty of Education and Teacher Training of IAIN Palopo, 2023)
Writing is consistently regarded as one of the most challenging language-learning abilities. This paper investigates the challenges Vietnamese students face in learning academic writing in English. Ninety-five students from grades 6 to 12 who have been studying English for several years were surveyed using a questionnaire. The questionnaire comprised 14 Likert-scale statements and one multiple-choice question to determine their interests, habits, and perspectives toward learning English. Most participants expressed a keen interest in learning languages but felt that their writing skills in English were not up to par, attributing this to inadequate time spent practicing. As a result, it is suggested that secondary school students in Vietnam increase their writing practice time in English and alter their learning routines and habits accordingly.